2014
DOI: 10.1074/jbc.m114.589440
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Protects Pancreatic Acinar Cells from Palmitoleic Acid-induced Cellular Injury

Abstract: Background: Palmitoleic acid is a major pancreatitis-inducing agent.Results: Insulin protected cells from palmitoleic acid (POA)-induced ATP depletion, inhibition of the plasma membrane calcium pump (PMCA), cytotoxic Ca2+ overload and necrosis.Conclusion: Insulin protects against acinar cell injury induced by pancreatitis-inducing agents.Significance: This provides an important therapeutic strategy for treating pancreatitis with insulin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…UFAs inhibit mitochondrial complexes I and V 1. While we noted early caspase 3/7 activation in acini, this was not sustained (results not shown), perhaps due to concurrent ATP depletion104 115 116 triggering the necrosis noted at 5 h. Noting this, and the dual annexin V and PI staining of PBMCs, TUNEL positivity in lungs and renal tubules (which are also KIM-1 positive), the likely mode of injury induced by UFAs is necro-apoptotic.…”
Section: Discussionmentioning
confidence: 64%
“…UFAs inhibit mitochondrial complexes I and V 1. While we noted early caspase 3/7 activation in acini, this was not sustained (results not shown), perhaps due to concurrent ATP depletion104 115 116 triggering the necrosis noted at 5 h. Noting this, and the dual annexin V and PI staining of PBMCs, TUNEL positivity in lungs and renal tubules (which are also KIM-1 positive), the likely mode of injury induced by UFAs is necro-apoptotic.…”
Section: Discussionmentioning
confidence: 64%
“…First, increasing extracellular magnesium reduces pancreatitis responses in rodent acinar cells including pathologic calcium signaling and lessens the severity of in vivo pancreatitis in rodent models113, 114; it now is being examined for its potential role in reducing PEP 112 . Insulin recently was shown to decrease calcium levels caused by induction of pancreatitis responses in acinar cells and reduce other cellular pancreatitis injuries 115, 116. These actions appear to be linked to a plasma-membrane calcium pump.…”
Section: Has Anything Been Identified In Animal Models That Clearly Imentioning
confidence: 99%
“…Epidemiological studies reported a positive correlation between high circulating 16:1n-7 levels and obesity (Gong et al, 2011), pancreatitis (Samad et al, 2014), hepatic steatosis (Lee et al, 2015), and cardiovascular disease (Warensjo et al, 2008). Other studies showed that sensitivity to insulin in peripheral tissues is not associated with the availability of 16:1n-7 in plasma of obese patients (Fabbrini et al, 2011), and that high levels of this fatty acid in red blood cells correlate with severity of inflammation (Perreault et al, 2014) and greater risk of diabetes (Zong et al, 2013).…”
Section: Introductionmentioning
confidence: 97%